Development of a compact light detection and ranging module - Ng, Kok Leong (2023)

(untitled)
Recent advancements in laser and detector technology have made it possible to create a compact Light Detection and Ranging, LiDAR system that is highly accurate and operates on low power. LiDAR systems consist of a laser source, photodetector, signal processor, and data processor. This research explores the potential of replacing the LiDAR Lite commercial unit's laser source with a smaller semiconductor laser. To achieve this, a complete prototype was developed using a miniature semiconductor laser called Vertical Cavity Surface Emitting Laser, VCSEL. The system was integrated with an Arduino UNO microcontroller and 3D-printed brackets. The laser used in the prototype is specifically characterized to meet the LiDAR system's requirements for laser power, wavelength, and beam shape. Testing was conducted in several stages to ensure the prototype's functionality. The data collected by the LiDAR prototype was analysed and presented as a Point Cloud, showing the position of points in X, Y, and Z coordinates. The system aims to provide a basis for future work.